A bedside swallowing screen for the identification of post-extubation dysphagia on the intensive care unit – validation of the Gugging Swallowing Screen (GUSS)—ICU - Claudia Troll; Michaela Trapl-Grundschober; Yvonne Teuschl; Adrien Cerrito; Montserrat Gallego Compte; Martin Siegemund (BMC Anesthesiology, 2023)
Abstract Purpose Screening for dysphagia at the intensive care unit (ICU) soon after extubation can prevent aspiration, pneumonia, lower mortality, and shorten re-feeding interval. This study aimed to modify the Gugging Swallowing Screen (GUSS), which was developed for acute stroke patients, and to validate it for extubated patients in the ICU. Methods In this prospective study, forty-five patients who had been intubated for at least 24 h were recruited consecutively at the earliest 24 h after extubation. The modified GUSS-ICU was performed twice by two speech and language therapists independently. Concurrently, gold standard the flexible endoscopic evaluation of swallowing (FEES) was performed by an otorhinolaryngologist. Measurements were conducted within a three-hour period; all testers were blinded to each other’s results. Results According to FEES, 36 of 45 (80%) participants were diagnosed with dysphagia; 13 of those were severe, 12 moderate, and 11 mild. Compared to FEES, the GUSS-ICU predicted dysphagia well (area under the curve for the initial rater pair: 0.923, 95% CI 0.832–1.000 and 0.923, 95% CI 0.836 -1.000 for the second rater pair). The sensitivity was 91.7% (95% CI 77.5–98.3%) and 94.4% (95% CI 81.3–99.3%); the specificity was 88.9% (51.8–99.7%) and 66.7% (29.9–92.5%); the positive predictive values were 97.1% (83.8–99.5%) and 91.9% (81.7–96.6%), and the negative predictive values were 72.7% (46.8–89%) and 75% (41.9–92.6%) for the first and second rater pairs, respectively. Dysphagia severity classification according to FEES and GUSS-ICU correlated strongly (Spearman’s rho: 0.61 for rater 1 and 0.60 for rater 2, p < 0.001). Agreement by all testers was good (Krippendorffs Alpha: 0.73). The interrater reliability showed good agreement (Cohen`s Kappa: 0.84, p < 0.001). Conclusion The GUSS-ICU is a simple, reliable, and valid multi-consistency bedside swallowing screen to identify post-extubation dysphagia at the ICU. Trial registration ClinicalTrials.gov Identifier: NCT04532398,31/08/2020.